2023
DOI: 10.1002/anie.202301925
|View full text |Cite
|
Sign up to set email alerts
|

Spin Manipulation in a Metal–Organic Layer through Mechanical Exfoliation for Highly Selective CO2Photoreduction

Abstract: Spin manipulation of transition-metal catalysts has great potential in mimicking enzyme electronic structures to improve activity and/or selectivity. However, it remains a great challenge to manipulate room-temperature spin state of catalytic centers. Herein, we report a mechanical exfoliation strategy to in situ induce partial spin crossover from highspin (s = 5/2) to low-spin (s = 1/2) of the ferric center. Due to spin transition of catalytic center, mixed-spin catalyst exhibits a high CO yield of 19.7 mmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“… Time-resolved PL decay spectra reveal that the average lifetime of [Ru(bpy) 3 ]Cl 2 is calculated as 413 ns, which is significantly longer than the lifetimes after the addition of NiTCPE- pstp and NiTCPE- stp , fitted to be 304 and 357 ns, respectively (Figure b). The shorter PL lifetime illustrates the photogenerated electrons can be transferred quickly, further indicating the stronger ability of NiTCPE- pstp for inhibiting the recombination of photogenerated carriers, thereby showing higher photocatalytic activity . Transient photocurrent responses were tested to further explore the separation efficiency of photogenerated electrons and holes, and the results showed that NiTCPE- pstp gives a good photoelectric response with the current density of 0.3 μA cm –2 , which is close to three times that of NiTCPE- stp , suggesting the significantly improved photogenerated charge separation after PSP (Figure c).…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… Time-resolved PL decay spectra reveal that the average lifetime of [Ru(bpy) 3 ]Cl 2 is calculated as 413 ns, which is significantly longer than the lifetimes after the addition of NiTCPE- pstp and NiTCPE- stp , fitted to be 304 and 357 ns, respectively (Figure b). The shorter PL lifetime illustrates the photogenerated electrons can be transferred quickly, further indicating the stronger ability of NiTCPE- pstp for inhibiting the recombination of photogenerated carriers, thereby showing higher photocatalytic activity . Transient photocurrent responses were tested to further explore the separation efficiency of photogenerated electrons and holes, and the results showed that NiTCPE- pstp gives a good photoelectric response with the current density of 0.3 μA cm –2 , which is close to three times that of NiTCPE- stp , suggesting the significantly improved photogenerated charge separation after PSP (Figure c).…”
Section: Results and Discussionmentioning
confidence: 95%
“…The shorter PL lifetime illustrates the photogenerated electrons can be transferred quickly, further indicating the stronger ability of NiTCPE-pstp for inhibiting the recombination of photogenerated carriers, thereby showing higher photocatalytic activity. 49 Transient photocurrent responses were tested to further explore the separation efficiency of photogenerated electrons and holes, and the results showed that NiTCPE-pstp gives a good photoelectric response with the current density of 0.3 μA cm −2 , which is close to three times that of NiTCPE-stp, suggesting the significantly improved photogenerated charge separation after PSP (Figure 4c). Moreover, electrochemical impedance spectroscopy measurements were performed to evaluate the internal resistance of the charge transfer process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Electronic structures determine the properties of materials, in which spin is an important inherent characteristic of electrons and can reflect the electronic structures of catalysts, dominating the chemical behavior of catalysts. , Recently, theoretical predictions and experiments have demonstrated that spin regulation enables improved catalytic performance. However, there have been very limited examples on spin regulation in photocatalysis, especially for photocatalytic CO 2 reduction, which is probably due to the grand challenge of regulating spin states in common photocatalysts. Currently, spin-state regulation in heterogeneous photocatalysts is mainly limited to the creation of structural vacancies and elemental doping. , Unfortunately, vacancies and dopants are not definitely catalytically active for CO 2 reduction, and sometimes, vacancies are even recombination centers of electrons and holes .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the spin state configuration of 3d transition metals can be a critical catalytic descriptor in electrocatalytic and photocatalytic systems. This is because spin state configuration is an index of the overall structure, energy, and redox profile of the catalyst, which determines the occupancy of e g orbital and impacts key reaction steps. ,, The spin state of transition-metal atom can be rationally modulated by the ligand field, magnetic field, or stress field. , Zhang et al have found that the Co atom experiences a transition from low-spin to high-spin states, generating more unpaired electrons under an external magnetic field . Such spin delocalization increases the charge transfer and orbital interactions between the sulfur species and the catalyst, thus lowering the energy barrier and increasing the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%